Electrochemical Sensor for Determination of Baicalin Based on Carbon Nanospheres - Shi, L.; Liu, W.; Wang, Z.F. (Asian Journal of Chemistry, 2015)
A novel electrochemical sensor based on the carbon nanospheres for the sensing of baicalin is reported. The electrochemical sensing platform was developed using the prepared carbon nanospheres. The colloidal carbon nanospheres were successfully synthesized by hydrothermal method. The resident porosity of porous carbon nanospheres will promote diffusion of baicalin molecules through interconnected micropores and will be benefited for increasing the detection sensitivity. The results show that the linear response range for baicalin is 0.1-2 μM, with the detection limit of 0.033 μM. The method maybe open up a new possibility for the wide spread use of electrochemical sensors for monitoring of flavonoid drugs owing to its advantages of simple preparation, low cost, high sensitivity.